Towards a Training Framework for Improved Assistive Mobile App Acceptance and Use Rates by Blind and Visually Impaired People - Paraskevi Theodorou; Apostolos Meliones (MDPI AG, 2020)
The development of mobile apps, which are either suitably adapted or especially designed for use by sensory-deprived people, have contributed significantly to the continuously increasing adoption of digital assistive technologies by people with disabilities. Throughout the design of two assistive navigation mobile apps for blind and visually impaired people (BVI), a set of everyday practices and psychological features of the BVIs with respect to the use of mobile technology was identified. Specifically, interviews with BVIs were held at the first stage of the design process. The analysis of the responses revealed that appropriate training of a BVI on how to use these apps plays significant role on the anticipated app adoption and use rate. This study presents the everyday practices and psychological features of the BVIs, as they were inferred from the analysis of the interviews. It is argued that these psychological features and practices must be considered in the development of training practices concerning the use of the proposed technology. Towards this direction, a framework for the adequate training of BVIs on the use of assistive mobile apps is presented. Consideration of this framework during the development of assistive mobile apps for BVIs could contribute towards higher adoption rates.